26 JANUARY, 2019 SOLAR FLARES DIAGNOSTICS BASED ON THE SOFT X-RAY EMISSION MEASURES - A. Sarsembayeva,; F. Belisarova,; M. Odsuren,; A. Sarsembay,; Zh. Kalymova, (Academic Scientific Journal of Computer Science, 2019)
In this paper, we recently analyzed solar flares registered on January 26, 2019. We have identified several physical quantities of solar flares and estimated reconnection rate of solar flares. To determine the physical parameters we used images taken with the AIA instrument on board SDO satellite at wavelengths AIA 193 Å, 131 Å, AIA 174 Å, SXT - pictures, HMI Magnetogram, GOES XRT-data.